(untitled) (Theatrum historiae, 2015)
The goal of the paper is present the changes of local administration during the Nazi occupation of the Czech lands using the example of Moravská Ostrava. The article deals with the annexation of 12 municipalities into Moravská Ostrava and its transformation to the statutatory city in 1941 and analyses its reasons and conseqeuenses.The particular attention is paid to the reflections of propaganda. The paper will also explore how to creation new Great Ostrava influenced by war and what role the city was designed in the German war economy. This changes were also the indication of the new tendencies in development of public administration in Czech lands. The aim of this paper is to show how the occupation authorities affecting the life of the Czech population in the cities of the Protectorate of Bohemia and Moravia. The analysis of particular examples based largely on unpublished archival sources and newspapers can be used as a base for forming more general conclusions concerning nature of the German occupation policy during Second World War.